2021
DOI: 10.1108/jec-12-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Neo-liberalism translated into preconditions for women entrepreneurs – two contrasting cases

Abstract: Purpose Contrasting two countries with different gender regimes and welfare states, Sweden and Tanzania, this paper aims to analyse how the institutional context affects the ways in which a neo-liberal reform agenda is translated into institutional changes and propose how such changes impact the preconditions for women’s entrepreneurship. Design/methodology/approach This study uses document analysis and previous studies to describe and analyse the institutions and the institutional changes. This paper uses S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Experiences from one context do not always translate well into another context (Xheneti, 2017). For example, Tillmar et al (2021aTillmar et al ( , 2021b showed that neoliberal entrepreneurship policy benefitted women in deeply patriarchal states such as Tanzania by providing women with an income of one's own and escape from dependence on a man, but in the well-developed Swedish welfare state, neoliberal entrepreneurship policy took a different routeit replaced public with private provision of welfare services, which paid women less than when publicly owned. Same economic ideology, but different outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiences from one context do not always translate well into another context (Xheneti, 2017). For example, Tillmar et al (2021aTillmar et al ( , 2021b showed that neoliberal entrepreneurship policy benefitted women in deeply patriarchal states such as Tanzania by providing women with an income of one's own and escape from dependence on a man, but in the well-developed Swedish welfare state, neoliberal entrepreneurship policy took a different routeit replaced public with private provision of welfare services, which paid women less than when publicly owned. Same economic ideology, but different outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the opposite end of the scale is a choice of new venues for professional advancement and business entrepreneurship opened by labour market liberalisation (Palalić et al, 2020; Ramadani et al, 2015; Tillmar et al, 2021). For example, gender differences in employment in Lithuania are also affected by the so-called revaluation of resources strategy that is available mostly to women but only to some degree to men (Fodor 1997; Ghodsee, 2005).…”
Section: Introductionmentioning
confidence: 99%